IT and the development of digital skills and competencies in education - Ordóñez de Pablos, Patricia 1975-; Lytras, Miltiadis D. 1973- (IGI Global, 2021)
"The book explores the new demands of labor markets in the digital economy, how educational institutions can respond to these new opportunities and threats, the development of new teaching and learning methods, and finally the development of digital skills and competences"--